Analisis Sifat Mekanik Batuan Terhadap Kemampugaruan Bulldozer Dan Kemampugalian Excavator Untuk Mencapai Target Produksi Overburden PT Berau Coal - Rosihan Pebrianto; Edwin Harsiga; Marwan Asof; Muhammad Dimas Thabrani (MINERAL, 2023)
The research was conducted at Pit Q, PT Berau Coal with the aim of determining the productivity parameters of bulldozer ripping, excavator productivity, and factors affecting ripping activities on sandstone. The results showed that the material in pit q was sandstone which had a ucs value of 6.26 Mpa and a seismic velocity of 1751.63 m/s so the crossripping method was used so that the material was dismantled smaller. Based on ripper productivity, the relationship between the depth of penetration of the shank ripper and the speed of the bulldozer is obtained, productivity of the excavator is smaller if the space used by the ripper increases, so that the size of the material produced will be larger and the digging time of the excavator will increase. The influence of ripper activities is the depth of penetration that affects the speed of the bulldozer, the use of ripping space affects the digging time performance of the excavator too. Factors of the performance of the ripper are trapped material, ripper tip wear, and operator skills.